Saving Mr. Wu [videorecording (DVD)] - Ding, Sheng, 1970-; Lau, Andy, 1961-; Liu, Ye, 1978-; Wang, Qianyuan, 1972- (Well Go USA Entertainment, 2016)
In this suspenseful crime thriller, Mr. Wu, a Hong Kong movie star, is kidnapped by six unpredictable criminals disguised as police officers. The story is based on the 2004 real life celebrity kidnapping case in China.